Calcium and Boron Foliar Application in the Production and Quality of Zucchini Seeds - Colombari, Lidiane Fernandes [UNESP] (2022)
Although there are fertilization recommendations for the cultivation of zucchini, there are just few researches about the effects of nutrients in seed production. Calcium and boron have a low mobility in plants, and some researches recommend foliar application for these nutrients. Thus, the objective of this research was to evaluate the foliar application of calcium and boron in the production and quality of zucchini seeds. The experimental design was randomized blocks with seven replications. Four treatments were evaluated: only calcium (0.2%) application, only boron (0.1%) application, combined application of calcium (0.2%) and boron (0.1%) and the control (without calcium and boron.) The following characteristics were evaluated: number of pollen grains per flower, hundred seeds weight; seed number and weight per fruit and seed physiological quality (germination; first germination count and speed of germination index - SGI). Only boron application reduced the number of seeds produced per fruit. The combined foliar application of calcium and boron, in addition to reducing the number of seeds, also reduced SGI. The calcium only application increased the amount of pollen per flower (superior to all other treatments) and also the number of seeds per fruit (compared to the combined application of calcium + boron), without affecting the quality of the zucchini seeds. So, it can be recomended the aplication of Ca during zucchini flowering for seed production.